A Micromotor Catheter for Intravascular Optical Coherence Tomography. (March 2015) - Wang, Tianshi; van Soest, Gijs; van der Steen, Antonius F.W.
ABSTRACT: We have developed a new form of intravascular optical coherence tomography (IV-OCT) that allows the extremely fast acquisition of high-resolution images of the coronary arteries. This process leads to much better image quality by eliminating cardiac motion artefacts and undersampling. It relies on a catheter that incorporates a synchronous micromotor with a diameter of 1.0 mm and a rotational speed of up to 5600 revolutions per second, enabling an IV-OCT frame rate of 5.6 kHz. This speed is matched by a wavelength-swept laser that generates up to 2.8 million image lines per second. With this setup, our team achieved IV-OCT imaging of up to 5600 frames per second (fps) in vitro and 4000 fps in vivo, deployed at a 100 mm·s −1 pullback velocity. The imaging session is triggered by the electrocardiogram of the subject, and can scan a coronary artery in the phase of the heartbeat where the heart is at rest, providing a name for this new technology: the "Heartbeat OCT."